Tick microbiome and pathogen acquisition altered by host blood meal - Swei, Andrea (ISME J, 2017)
Lyme disease, a zoonotic disease, is the most prevalent vector-borne disease in the Northern Hemisphere. Diversity of the vector (tick) microbiome can impact pathogen transmission, yet the biotic and abiotic factors that drive microbiome diversity are largely unresolved, especially under natural, field conditions. We describe the microbiome of Ixodes pacificus ticks, the vector for Lyme disease in the western United States, and show a strong impact of host blood meal identity on tick microbiome species richness and composition. Western fence lizards, a host that is refractory to the Lyme disease pathogen, significantly reduces microbiome diversity in ticks relative to ticks that feed on a mammalian reservoir host. Host blood meal-driven reduction of tick microbiome diversity may have lifelong repercussions on I. pacificus vector competency and ultimately disease dynamics.